Eloquent Silence The Doctrine of God in the Synopsis of Purer Theology - te Velde, Dolf (2012)
This article sketches the theological profile of the Synopsis Purioris Theologiae (1625) by focusing on its exposition of the doctrine of God. Earlier disputations by Leiden theologians Franciscus Junius (1545–1602) and Franciscus Gomarus (1563–1641) are discussed as a background for the theology of Antonius Thysius (1565–1640), the author of the disputation in the Synopsis on God’s nature and attributes. For a further specification of the doctrinal position presented in the Synopsis, it is contrasted with the more innovative accounts proposed by Jacob Arminius (1559–1609) in his disputation “De natura Dei” (1603) and by Conrad Vorstius (1569–1622) in his Tractatus theologicus de Deo (1606). This analysis yields the conclusion that both Arminius and Vorstius advocated a structural differentiation between God’s inner essence and his outward operations, which leaves room for human freedom and independence. While the Synopsis does not explicitly discuss their views, in its own formulations itmaintains the common Reformed orthodox notion of divine simplicity, and keeps the balance between—on the one hand—the (hypothetical) necessity of God’s foreknowledge and decree, and—on the other hand—the contingency and freedom in the created world.
Keywords: Synopsis -- doctrine of God -- Reformed scholasticism -- Antonius Thysius -- Franciscus Junius -- Franciscus Gomarus -- Jacob Arminius -- Conrad Vorstius -- Socinianism -- necessity -- contingency